Diaphragm and lithium ion battery
By setting up ceramic layers with different liquid absorption capabilities in the lithium-ion battery separator, the liquid lean problem in the middle area of the lithium-ion battery pole is solved, the circulation performance and safety of the battery are improved, the battery life is extended and maintenance costs are reduced.
Patent Information
- Application Number
- CN202411395116.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-27
AI Technical Summary
Lithium-ion batteries are prone to black spot lithium-ion separation during large-scale charging and discharging, resulting in reduced battery performance and safety hazards. The existing technology is difficult to effectively solve the liquid lean problem in the middle area of the pole sheet.
By providing ceramic layers with different liquid absorption abilities in the separator, the liquid absorption rate of the first ceramic layer is controlled to be higher than that of the second ceramic layer, and the distribution of the electrolyte is optimized to ensure that the electrolyte is evenly distributed in the electrode sheet, especially in the middle area.
It significantly improves the distribution of electrolyte on the electrode plate, reduces the occurrence of lithium-ion black spots, improves the circulation performance and safety of lithium-ion batteries, extends the service life of the battery, and reduces maintenance and replacement costs.
Smart Images

Figure CN119208923A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a diaphragm and a lithium ion battery comprising the diaphragm. Background Art
[0002] As a widely used energy storage device, lithium-ion batteries have the advantages of high energy density, long cycle life and low self-discharge. However, during the high-rate charge and discharge of lithium-ion batteries, there is a common problem, that is, black spots and lithium precipitation are prone to appear inside the battery. Black spots and lithium precipitation not only affect the performance of the battery, but also easily cause internal short circuits in the battery, which in turn cause safety hazards.
[0003] At present, although some technologies have been tried to solve similar problems, such as improving the injection process and adjusting the electrolyte formula, these technical methods often cannot specifically solve the problem of poor liquid in the middle area of the electrode. For example, the traditional approach to improving the injection process includes optimizing the injection speed, pressure, temperature and injection path to ensure that the electrolyte can penetrate more evenly into the electrode. However, due to the complexity of the electrode structure and the interaction between the electrolyte and the electrode material, these process improvements are still difficult to completely solve the problem of poor liquid in the middle area; adjusting the electrolyte formula is another common solution strategy. By changing the composition, concentration, type and content of the electrolyte, the physical and chemical properties of the electrolyte, such as viscosity, surface tension, wettability, etc., can be affected, thereby improving the wettability and distribution uniformity of the electrolyte on the electrode. However, this method also faces challenges, because the electrolyte formula needs to take into account multiple performance requirements, such as the energy density, cycle stability, safety, etc. of the battery, so it is often difficult to solve the problem of poor liquid without sacrificing other performance. Summary of the invention
[0004] Research has found that black spots are formed on the pole pieces of lithium-ion batteries. These spots are mainly formed by abnormal deposition of lithium ions in the poor liquid area during the charge and discharge process. The poor liquid area often appears in the middle area of the pole piece. The poor liquid area exists because the electrolyte fails to fully infiltrate or distribute in this area, which will cause the lithium ions to be unable to migrate normally during the charge and discharge process, thus causing the black spot lithium precipitation problem.
[0005] The present invention provides a diaphragm, which controls the liquid absorption capacity of the ceramic layer particles in the diaphragm, optimizes the distribution of the electrolyte in the diaphragm, improves the problem of poor liquid in the middle area of the pole piece, thereby reducing the occurrence of black spot lithium precipitation and improving the cycle performance and safety of the lithium-ion battery. In view of this, the inventor of the present invention proposes the following technical solution:
[0006] A first aspect of the present invention provides a diaphragm, which includes a substrate, a ceramic layer located on one side or both sides of the substrate, and a coating layer located on the surface of the substrate and / or on the surface of the ceramic layer. The ceramic layer includes a first ceramic layer and a second ceramic layer. The first ceramic layer is located in the middle area of the substrate surface, and the second ceramic layer is located in the edge area of the substrate surface or on the surface of the first ceramic layer and the edge area of the surface of the substrate. The liquid absorption rate of the first ceramic layer is greater than the liquid absorption rate of the second ceramic layer.
[0007] A second aspect of the present invention provides a lithium ion battery, which includes the separator described in the first aspect of the present invention.
[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0009] The present invention controls the liquid absorption of the ceramic layer in the diaphragm so that the liquid absorption of the first ceramic layer is greater than the liquid absorption of the second ceramic layer, thereby significantly improving the distribution of the electrolyte on the electrode sheet (wherein the electrode sheet includes a positive electrode sheet and a negative electrode sheet, and the positive electrode sheet and the negative electrode sheet are collectively referred to as the electrode sheet hereinafter), making the distribution of the electrolyte on the electrode sheet more uniform, especially in the middle area of the electrode sheet, thereby ensuring that lithium ions can be effectively migrated during the charging and discharging process, improving the charging and discharging efficiency of the lithium-ion battery, reducing the occurrence of black spot lithium precipitation, reducing the risk of internal short circuit of the lithium-ion battery, improving the safety performance of the lithium-ion battery, reducing the performance degradation of the battery during long-term use, improving the cycle performance of the lithium-ion battery, and extending the service life of the lithium-ion battery. In addition, it can also reduce the maintenance cost and replacement frequency of the battery, thereby saving money for users.
[0010] In summary, the present invention improves the distribution of electrolyte on the electrode and reduces black spot lithium precipitation by optimizing the liquid absorption capacity of the diaphragm ceramic layer, thereby improving the cycle performance and safety of the lithium-ion battery, thereby extending the service life of the lithium-ion battery and potentially saving costs.
[0011] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1The figure shows one of the cross-sectional schematic diagrams of the diaphragm of the present invention along the width direction.
[0014] Figure 2 The second schematic cross-sectional view of the diaphragm of the present invention along the width direction is shown.
[0015] Figure 3 The figure shows one of the schematic top views of the first ceramic layer in the diaphragm of the present invention.
[0016] Figure 4 The figure shows the second schematic top view of the first ceramic layer in the diaphragm of the present invention.
[0017] Figure 5 The third schematic top view of the first ceramic layer in the diaphragm of the present invention is shown.
[0018] Figure 6 The fourth schematic top view of the first ceramic layer in the diaphragm of the present invention is shown.
[0019] Figure 7 The fifth schematic top view of the first ceramic layer in the diaphragm of the present invention is shown.
[0020] Figure 8 FIG. 4 is a schematic diagram of a wound battery cell according to an embodiment of the present invention.
[0021] Fig. 9 FIG. 1 is an interface diagram of a negative electrode sheet according to an embodiment of the present invention.
[0022] Fig.10 Shown is a pair of proportional interface diagrams of negative electrode sheets. DETAILED DESCRIPTION
[0023] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.
[0024] A first aspect of the present invention provides a diaphragm, which includes a substrate, a ceramic layer located on one side or both sides of the substrate, and a coating layer located on the surface of the substrate and / or on the surface of the ceramic layer. The ceramic layer includes a first ceramic layer and a second ceramic layer. The first ceramic layer is located in the middle area of the substrate surface, and the second ceramic layer is located in the edge area of the substrate surface or on the surface of the first ceramic layer and the edge area of the surface of the substrate. The liquid absorption rate of the first ceramic layer is greater than the liquid absorption rate of the second ceramic layer.
[0025] like Figure 1 and Figure 2As shown, the diaphragm includes a substrate 1, a ceramic layer 2 located on one side of the substrate 1, and a rubber coating layer 3 located on the substrate surface and / or on the ceramic layer 2 surface. The ceramic layer 2 includes a first ceramic layer 21 and a second ceramic layer 22. The first ceramic layer 21 is located in the middle area of the substrate 1 surface, and the second ceramic layer 22 is located in the edge area of the substrate 1 surface or on the surface of the first ceramic layer 21 and the edge area of the substrate 1 surface. Figure 1 It can be seen that the first ceramic layer 21 is located in the middle area of the surface of the substrate 1, and the second ceramic layer 22 is located in the edge area of the surface of the substrate 1 and the surface of the first ceramic layer 21. The middle area is the area along the width direction of the diaphragm.
[0026] In the present invention, ceramic layers with different liquid absorption capabilities are respectively arranged in the middle area and edge area of the diaphragm, and the liquid absorption rate of the first ceramic layer is controlled to be greater than the liquid absorption rate of the second ceramic layer, so that the electrolyte can more easily penetrate from the edge to the middle position and more electrolyte is retained in the middle area, thereby realizing the gradient distribution of the electrolyte in the electrode piece, solving the problem of black spot lithium precipitation caused by the appearance of a lean liquid area in the middle position of the electrode piece, improving the safety performance of the battery, and at the same time ensuring that lithium ions can be effectively migrated during the charging and discharging process, thereby improving the charging and discharging efficiency of the lithium-ion battery, and the gradient distribution of the electrolyte in the middle and edge areas of the electrode piece reduces the performance degradation of the battery during long-term use, improves the cycle performance of the lithium-ion battery, and extends the service life of the lithium-ion battery; moreover, by arranging the first ceramic layer and the second ceramic layer, the structure of the two ceramic layers can ensure the liquid absorption amount of the battery without affecting the weight energy density of the battery.
[0027] In the present invention, ceramic layers with different liquid absorption capacities are respectively arranged in the middle area and the edge area of the separator, and the liquid absorption rate of the first ceramic layer is controlled to be greater than the liquid absorption rate of the second ceramic layer. Compared with the prior art, the battery has higher safety performance and cycle performance. In order to further improve the effect, one or more of the technical features can be further optimized.
[0028] In the present invention, the middle area is the middle position along the width direction of the substrate, and the edge area is the two side positions along the width direction of the substrate. Figure 3 As shown, the middle area 4 is located in the middle position along the width direction a of the substrate, and the edge areas 5 are located at both sides along the width direction a of the substrate. Figure 3As shown, along the width direction of the substrate, the substrate may include a middle area located in the middle position and two edge areas located on both sides. It can be understood that the middle area can be located in the middle of the substrate along the width direction relative to the edge areas, or can be located at a position slightly above or below the substrate along the width direction, but the middle area must be located between the edge areas on both sides.
[0029] The projection formed by the first ceramic layer on the surface of the substrate can be a regular pattern or an irregular pattern. Figure 3 As shown, the projection formed by the first ceramic layer on the surface of the substrate is a regular pattern; Figure 4 and Figure 5 As shown, the projection formed by the first ceramic layer on the surface of the substrate is an irregular pattern. The projection formed by the first ceramic layer on the surface of the substrate is a regular pattern or an irregular pattern, which can optimize the distribution of the electrolyte in the electrode, solve the problem of the lean liquid area in the middle position, and improve the safety performance and cycle performance of the battery.
[0030] In one example, the projection formed by the first ceramic layer on the surface of the substrate is a square (eg Figure 3 As shown), striped (as Figure 6 As shown), polygons (such as Figure 5 as shown) or irregular shapes (such as Figure 4 , Figure 7 shown).
[0031] In one example, the projection formed by the first ceramic layer on the surface of the substrate is a continuous pattern along the length direction of the diaphragm (eg Figure 3 , Figure 4 , Figure 5 as shown) or non-continuous graphics (such as Figure 6 , Figure 7 The projection formed by the first ceramic layer on the surface of the substrate is a continuous pattern or a discontinuous pattern along the length direction of the diaphragm, which can solve the problem of black spot lithium precipitation caused by the appearance of a lean liquid area in the middle of the pole piece, thereby improving the safety performance and cycle performance of the battery and extending the service life of the battery.
[0032] In one example, the first ceramic layer includes a plurality of periodically arranged coating areas and blank areas, wherein the coating area is the first ceramic layer, the coating area corresponds to the plane area of the wound battery cell, and the blank area corresponds to the bending area of the wound battery cell. Figure 8 As shown, the wound battery cell includes a flat area 31 and a bending area 32 , the coating area corresponds to the flat area 31 of the wound battery cell, and the blank area corresponds to the bending area 32 of the wound battery cell.
[0033] It can be understood that the surface of the first ceramic layer is coated with the second ceramic layer, and the second ceramic layer can fill the blank area of the first ceramic layer, so the blank area in the first ceramic layer is the second ceramic layer.
[0034] In one example, the ratio of the area of the coated area to the area of the blank area is (50%-100%):(50%-0) (e.g., 50%:50%, 60%:40%, 70%:30%, 80%:20%, 90%:10% or 100%:0). It is understood that the area ratio of the coated area can be within the range of 50%-100%, and the area ratio of the blank area can be within the range of 50%-0, but it needs to be satisfied that the sum of the area ratio of the coated area and the area ratio of the blank area is 100%.
[0035] By controlling the ratio of the area of the coating area to the area of the blank area within the above range, the liquid absorption rate of the middle area of the finished diaphragm can be greater than the liquid absorption rate of the edge area. The higher liquid absorption rate in the middle area helps to balance the electrolyte distribution of the entire diaphragm, reduce the electrolyte depletion phenomenon in the middle area, and thus significantly improve black spot lithium precipitation during the cycle.
[0036] In one example, the ratio of the area of the coated area to the area of the blank area is (70%-100%):(30%-0).
[0037] In one example, the projection formed by the first ceramic layer on the surface of the substrate is a regular continuous pattern along the length direction of the diaphragm (eg Figure 3 , Figure 5 shown).
[0038] In one example, the projection formed by the first ceramic layer on the surface of the substrate is a regular discontinuous pattern along the length direction of the diaphragm (eg Figure 6 shown).
[0039] In one example, the projection formed by the first ceramic layer on the surface of the substrate is an irregular continuous pattern along the length direction of the diaphragm (eg Figure 4 shown).
[0040] In one example, the projection formed by the first ceramic layer on the surface of the substrate is an irregular non-continuous pattern along the length direction of the diaphragm (eg Figure 7 shown).
[0041] In one example, the liquid absorption rate of the first ceramic layer is 100%-200% (e.g., 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190% or 200%).
[0042] In one example, the liquid absorption rate of the first ceramic layer is 120%-170%.
[0043] In one example, the liquid absorption rate of the second ceramic layer is 40%-110% (eg, 40%, 50%, 60%, 70%, 80%, 90%, 100% or 110%).
[0044] In one example, the liquid absorption rate of the second ceramic layer is 50%-90%.
[0045] In the present invention, the liquid absorption rate of the first ceramic layer or the second ceramic layer can be tested by the following method: under normal temperature and low humidity environment, cut 10 pieces of samples per unit area (such as 20mm*20mm) containing only the first ceramic layer or only the second ceramic layer from the diaphragm removed from the battery, for example, cut 10 pieces of samples per unit area (such as 20mm*20mm) containing only the first ceramic layer, weigh the weight and record it as w1, bake at 110°C for 30 minutes, weigh the weight after drying and record it as w2, liquid absorption rate = (w1-w2) / w2*100%, take the average value of five times respectively as the liquid absorption rate of the first ceramic layer. The liquid absorption rate of the second ceramic layer can also be measured by the above method.
[0046] The liquid absorption rate of the first ceramic layer or the second ceramic layer can also be tested by the following method: Under normal temperature and low humidity environment, take 10 20mm*20mm samples containing only the first ceramic layer or only the second ceramic, for example, take 10 20mm*20mm samples containing only the first ceramic layer and place them on an electronic balance, weigh the sample and record the weight as m1, place the sample in a beaker containing 200mL of organic solvent (EMC), and ensure that the sample is completely immersed in the organic solvent. After a fixed time of 10 minutes, take out the sample immersed in the organic solvent and weigh it as m2. Then the liquid absorption rate = (m2-m1) / m1*100%, measure 5 times respectively and take the average value as the liquid absorption rate of the first ceramic layer. The liquid absorption rate of the second ceramic layer can also be measured by the above method.
[0047] In one example, the liquid absorption rate of the first ceramic particles is 100%-200% (e.g., 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190% or 200%).
[0048] In one example, the liquid absorption rate of the first ceramic particles is 120%-160%.
[0049] In one example, the liquid absorption rate of the second ceramic particles is 40%-100% (eg, 40%, 50%, 60%, 70%, 80%, 90% or 100%).
[0050] In one example, the liquid absorption rate of the second ceramic particles is 50%-80%.
[0051] The liquid absorption rate can be tested in the following manner: weigh the ceramic particles as M0, put them into ethyl methyl carbonate (EMC) solvent, let them stand for 1 hour, take out the sample, weigh it as M1, and the liquid absorption rate = (M1-M0) / M0*100%.
[0052] It can be understood that by controlling the liquid absorption rate of the first ceramic particles to be greater than the liquid absorption rate of the second ceramic particles, it can be achieved that the liquid absorption rate of the first ceramic layer is greater than the liquid absorption rate of the second ceramic layer.
[0053] In one example, the liquid absorption rate of the first ceramic layer is 120%-170%, and the liquid absorption rate of the first ceramic particles is 120%-160%.
[0054] In one example, the liquid absorption rate of the second ceramic layer is 50%-90%, and the liquid absorption rate of the second ceramic particles is 50%-80%.
[0055] In one example, the width of the first ceramic layer is w1, in μm, and the width of the substrate is w2, in μm, and the diaphragm satisfies the following relationship: w1≥w2 / 2.
[0056] The width w1 of the first ceramic layer is the width of the first ceramic layer along the width direction of the diaphragm (eg Figure 1 The width w1 of the first ceramic layer is the length in the width direction a). When the projection formed by the first ceramic layer on the surface of the substrate is an irregular pattern, the width w1 of the first ceramic layer is the average of the length at the widest position and the length at the narrowest position. The width w2 of the substrate is the length of the substrate along the width direction of the diaphragm.
[0057] Controlling the diaphragm to satisfy w1≥w2 / 2 can ensure that there is enough electrolyte in the middle of the diaphragm, thereby ensuring that there will be no problem of poor electrolyte in the middle of the electrode during the battery cycle, thereby improving the battery's cycle performance and safety performance and extending the battery's service life.
[0058] The width of the second ceramic layer may be the same as or different from the width of the substrate.
[0059] In one example, the width of the second ceramic layer is the same as the width of the substrate.
[0060] In one example, the porosity of the first ceramic layer is greater than the porosity of the second ceramic layer. The porosity of the first ceramic layer located in the middle is higher than that of the second ceramic layer, which enables more electrolyte to flow to the middle of the electrode, optimizes the distribution of the electrolyte in the electrode, and makes the electrolyte more evenly distributed in the electrode, thereby improving the safety performance and cycle performance of the battery.
[0061] In one example, the porosity K1 of the first ceramic layer is 40%-90% (eg, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%).
[0062] In one example, the porosity K1 of the first ceramic layer is 50%-65%.
[0063] In one example, the porosity K2 of the second ceramic layer is 10%-40% (eg, 10%, 15%, 20%, 25%, 30%, 35% or 40%).
[0064] In one example, the porosity K2 of the second ceramic layer is 25%-35%.
[0065] In one example, the porosity of the first ceramic layer is greater than the porosity of the second ceramic layer, and the porosity K1 of the first ceramic layer is 40%-90%, and the porosity K2 of the second ceramic layer is 10%-40%. By controlling the porosity of the first ceramic layer and the second ceramic layer at the same time, and making the porosity of the first ceramic layer located in the middle area greater than the porosity of the second ceramic layer, the diaphragm can absorb and retain more electrolyte, which can not only improve the ionic conductivity of the battery, provide more ion transmission channels, thereby reducing the internal resistance of the battery, reduce the heat generated by the battery during charging and discharging, solve the problem of fast consumption of electrolyte due to high temperature in the middle area, improve the thermal management ability of the battery (by optimizing the distribution and retention of the electrolyte, the risk of thermal runaway caused by high temperature can be reduced, and the overall thermal management ability of the battery can be improved), and the cycle life of the battery under high rate charging and discharging conditions can be extended. At the same time, on the premise of ensuring that the electrolyte in the edge area is sufficient to meet the battery cycle, more electrolyte flows to the middle area of the battery, and the risk of deformation and damage of the diaphragm when subjected to external force can be reduced.
[0066] In one example, the air permeability of the first ceramic layer is 20s / 100ml-100s / 100ml (for example, 20s / 100ml, 30s / 100ml, 40s / 100ml, 50s / 100ml, 60s / 100ml, 70s / 100ml, 80s / 100ml, 90s / 100ml or 100s / 100ml).
[0067] In one example, the air permeability of the first ceramic layer is 50s / 100ml-90s / 100ml.
[0068] In one example, the air permeability of the second ceramic layer is 170s / 100ml-370s / 100ml (for example, 170s / 100ml, 190s / 100ml, 200s / 100ml, 210s / 100ml, 230s / 100ml, 250s / 100ml, 280s / 100ml, 300s / 100ml, 320s / 100ml, 350s / 100ml or 370s / 100ml).
[0069] In one example, the air permeability of the second ceramic layer is 210s / 100ml-300s / 100ml.
[0070] In the present invention, the air permeability value can be obtained by testing in the following way: first, place the substrate on a testing instrument (Asahi Seiko air permeability tester), squeeze 100 ml of gas from one air chamber to another air chamber at a constant pressure (for example, 0.05 MPa), and record the time taken for the gas to pass as S1. Then, the diaphragm coated with ceramic particles on the substrate is measured in the above manner, and the gas passing time is recorded as S2. The air permeability value of the ceramic layer S=S2-S1. For example, if the substrate is coated with the first ceramic particles and tested by the above method, and the gas passing time is S21, then the air permeability value of the first ceramic layer is S21-S1; if the substrate is coated with the second ceramic particles and tested by the above method, and the gas passing time is S22, then the air permeability value of the second ceramic layer is S22-S1.
[0071] In one example, the air permeability of the first ceramic layer is 50s / 100ml-90s / 100ml, and the air permeability of the second ceramic layer is 210s / 100ml-300s / 100ml. Controlling the air permeability of the first ceramic layer and the air permeability of the second ceramic layer within the above range can make the air permeability of the first ceramic layer (located in the middle area) lower, so that the first ceramic layer can absorb and retain the electrolyte faster, ensuring that the middle area can retain more electrolyte, thereby solving the problem of fast electrolyte consumption due to high temperature in the middle area, thereby optimizing the distribution of the electrolyte, improving ionic conductivity, reducing battery heating, extending cycle life, improving battery cycle performance stability and enhancing mechanical stability.
[0072] In one example, the first ceramic particles include particles having a spherical honeycomb through-pore structure.
[0073] The particles with spherical honeycomb through-hole structure can be prepared by the following method: using the sol-gel method combined with the spherical template technology to directly prepare ceramic particles with micron-sized spherical honeycomb through-hole structure. Specifically, the following steps are included: ① Sol preparation: select a suitable ceramic precursor (for example, tetrabutyl titanate (TBOT)), and prepare a stable sol system in a solvent through hydrolysis and polycondensation reaction; ② Template selection and treatment: select a template with a micron-sized spherical pore structure, such as a polystyrene microsphere self-assembly template, and perform surface treatment to enhance its adsorption to the sol; ③ Sol impregnation and gelation: impregnate the sol evenly into the template, and control the conditions to make the sol gel in the template pores to form a ceramic precursor gel; ④ Template removal: use chemical dissolution or calcination methods to accurately remove the template and retain the ceramic skeleton with a spherical honeycomb through-hole structure. ⑤ Sintering molding: sinter the ceramic skeleton at high temperature to densify it and form the final micron-sized spherical honeycomb through-hole ceramic particles.
[0074] In one example, the first ceramic particles are particles with a spherical honeycomb through-hole structure.
[0075] In one example, the average particle size D1 of the first ceramic particles is smaller than the average particle size D2 of the second ceramic particles.
[0076] In one example, 0.1 μm≤D1≤0.5 μm (eg, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm).
[0077] In an example, 0.6 μm ≤ D2 ≤ 1.4 μm (eg, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, or 1.4 μm).
[0078] In the present invention, the average particle size can be obtained by testing by the following method: using a TESCAN VEGA3 scanning electron microscope, mode secondary electron imaging, acceleration voltage 20kv, magnification 5000 times, scanning range 25μm*25μm, randomly selecting 50 particles within the range to measure the size of the particles, calculating the particle size from the starting point to the end point of the particle (the starting point to the longest end point of the particle), and the average size of the 50 particles is the average particle size.
[0079] In one example, the median particle size Dv150 of the first ceramic particles is less than the median particle size Dv250 of the second ceramic particles.
[0080] In one example, 0.1 μm ≤ Dv150 ≤ 0.5 μm (eg, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, or 0.5 μm).
[0081] In an example, 0.6 μm ≤ Dv250 ≤ 1.4 μm (eg, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, or 1.4 μm).
[0082] In one example, the specific surface area BET1 of the first ceramic particles is greater than the specific surface area BET2 of the second ceramic particles.
[0083] In one example, 8m 2 / g≤BET1≤20m 2 / g (e.g., 8m 2 / g, 10m 2 / g, 12m 2 / g, 15m 2 / g, 18m 2 / g or 20m 2 / g).
[0084] In one example, 2m 2 / g≤BET2≤7m 2 / g (for example, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g or 7m 2 / g).
[0085] In one example, the first ceramic particles include particles with a spherical honeycomb through-hole structure, and the average particle size D1 of the first ceramic particles is 0.1 μm≤D1≤0.5 μm, and the specific surface area BET1 of the first ceramic particles is 8 m 2 / g≤BET1≤20m 2 / g. Since the first ceramic particles have a large specific surface area and a small average particle size, the first ceramic particles can absorb more electrolyte at this time, and the first ceramic particles include particles with a spherical honeycomb through-hole structure, which can further promote the penetration and diffusion of the electrolyte in the first ceramic particles, thereby increasing the liquid absorption of the first ceramic particles and the liquid retention of the first ceramic layer, thereby further increasing the liquid absorption speed and liquid retention capacity of the diaphragm and improving the cycle stability of the battery.
[0086] In one example, the average particle size D2 of the second ceramic particles is 0.6 μm ≤ D2 ≤ 1.4 μm, and the specific surface area BET2 of the second ceramic particles is 2 m 2 / g≤BET2≤7m 2 / g. Since the second ceramic particles have a larger average particle size and better mechanical properties, they can enhance the mechanical strength and puncture strength of the edge area of the diaphragm. In addition, the second ceramic particles have a smaller specific surface area and a poorer liquid retention capacity than the first ceramic particles, which can make it easier for the electrolyte to penetrate from the edge area to the middle area.
[0087] In one example, the first ceramic particles include particles with a spherical honeycomb through-hole structure, and the average particle size K1 of the first ceramic particles is 0.1 μm≤D1≤0.5 μm, and the specific surface area BET1 of the first ceramic particles is 8 m 2 / g≤BET1≤20m 2 / g, and the average particle size K2 of the second ceramic particles is 0.6 μm≤D2≤1.4 μm, and the specific surface area BET2 of the second ceramic particles is 2 m 2 / g≤BET2≤7m 2 / g, the average particle size D1 of the first ceramic particles is less than the average particle size D2 of the second ceramic particles, and the specific surface area BET1 of the first ceramic particles is greater than the specific surface area BET2 of the second ceramic particles. At this time, the high liquid absorption and liquid retention capacity of the middle area and the high mechanical strength of the edge area are combined at the same time, thereby optimizing the overall performance of the diaphragm, further improving the cycle performance and safety performance of the battery, and ensuring that the electrolyte is not deficient in the middle area during the long cycle of the battery, thereby avoiding the problems of black spots and lithium precipitation due to insufficient electrolyte in the battery.
[0088] In one example, the porosity of the first ceramic layer is greater than the porosity of the second ceramic layer, the porosity K1 of the first ceramic layer is 50%-65%, the permeability of the first ceramic layer is 50s / 100ml-90s / 100ml, the first ceramic particles include particles with a spherical honeycomb through-hole structure, the porosity K2 of the second ceramic layer is 25%-35%, the permeability of the second ceramic layer is 210s / 100ml-300s / 100ml, the average particle size K1 of the first ceramic particles is less than the average particle size K2 of the second ceramic particles, and the specific surface area BET1 of the first ceramic particles is greater than the specific surface area BET2 of the second ceramic particles.
[0089] In one example, the first ceramic particles include one or more of aluminum oxide, magnesium oxide, silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, magnesium nitride, tin dioxide, magnesium hydroxide, boehmite, and calcium carbonate.
[0090] In one example, the first ceramic particles include one or more of aluminum oxide (Al2O3), boehmite (AlOOH) and silicon dioxide (SiO2). Aluminum oxide (Al2O3), boehmite (AlOOH) and silicon dioxide (SiO2) have stronger liquid absorption capacity. For example, the first ceramic layer including aluminum oxide can significantly improve the wettability and liquid absorption capacity of the diaphragm to the electrolyte, thereby improving the cycle performance and safety of the battery; the first ceramic layer including boehmite, because boehmite contains crystal water, has good affinity for polar solvents in the electrolyte, which helps to improve the liquid absorption rate and liquid retention performance of the diaphragm; the first ceramic layer including silicon dioxide, because silicon dioxide has a porous structure, the structure makes silicon dioxide have a larger specific surface area, can absorb more electrolyte, and the presence of silicon hydroxyl (Si-OH) makes silicon dioxide have good affinity for polar solvents, which can further improve the liquid absorption rate and liquid retention performance of the diaphragm. Therefore, when the first ceramic particles include one or more of alumina (Al2O3), boehmite (AlOOH) and silica (SiO2), the first ceramic particles can provide more wetting points, which helps to evenly distribute the electrolyte in the diaphragm, thereby improving the cycle performance and safety performance of the battery.
[0091] In one embodiment, the liquid absorption rate of the first ceramic particles is 120%-160%, the average particle size D1 of the first ceramic particles is 0.1 μm≤D1≤0.5 μm, and the specific surface area BET1 of the first ceramic particles is 8 m 2 / g≤BET1≤20m 2 / g, the first ceramic particles include particles of a spherical honeycomb through-hole structure, the first ceramic particles include one or more of alumina (Al2O3), boehmite (AlOOH) and silicon dioxide (SiO2), the porosity K1 of the first ceramic layer is 50%-65%, the air permeability of the first ceramic layer is 50s / 100ml-90s / 100ml, and the thickness h1 of the first ceramic layer is 0.5μm≤h1≤2μm. By controlling the above technical features, the liquid absorption and liquid retention performance of the first ceramic layer can be improved.
[0092] In one example, the second ceramic particles include one or more of aluminum oxide, magnesium oxide, silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, magnesium nitride, tin dioxide, magnesium hydroxide, boehmite, and calcium carbonate.
[0093] In one example, the first ceramic particles are the same as or different from the second ceramic particles. When the first ceramic particles are the same as the second ceramic particles, the average particle size and / or specific surface area of the first ceramic particles and the second ceramic particles can be adjusted to satisfy the liquid absorption of the first ceramic particles>the liquid absorption of the second ceramic particles, and the problem of black spots and lithium precipitation in the middle area of the electrode can also be solved.
[0094] In one embodiment, the liquid absorption rate of the second ceramic particles is 50%-80%, the average particle size D2 of the second ceramic particles is 0.6 μm≤D2≤1.4 μm, and the specific surface area BET2 of the second ceramic particles is 2 m 2 / g≤BET2≤7m 2 / g, the second ceramic particles include one or more of aluminum oxide, magnesium oxide, silicon dioxide, titanium dioxide, zirconium dioxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, magnesium nitride, tin dioxide, magnesium hydroxide, boehmite and calcium carbonate, the porosity K2 of the second ceramic layer is 25%-35%, the air permeability of the second ceramic layer is 210s / 100ml-300s / 100ml, and the thickness h2 of the second ceramic layer is 1μm≤h2≤10μm. By controlling the above-mentioned technical features, the liquid absorption of the second ceramic layer can be controlled within a suitable range, so that the liquid absorption of the first ceramic layer is greater than the liquid absorption of the second ceramic layer, thereby solving the problem of black spot lithium precipitation in the middle area of the pole piece due to poor liquid, thereby improving the safety performance and cycle performance of the battery.
[0095] In one example, the thickness of the first ceramic layer is h1, in μm, and the thickness of the second ceramic layer is h2, in μm, then the diaphragm satisfies the following relationship: A = h1 × D1 × BET1, B = h2 × D2 × BET2, then 0.5 ≤ B / A ≤ 11 (for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or 11). Controlling the diaphragm to satisfy the above relationship can ensure that during the battery cycle, when the electrolyte on the surface of the upper second ceramic layer in the middle region is consumed, the electrolyte in the lower first ceramic layer can be replenished to the surface of the upper second ceramic layer in time due to the concentration difference between the two, thereby maintaining a good state of the interface between the diaphragm and the electrode, avoiding the black spot lithium precipitation phenomenon caused by the lack of interface electrolyte during the cycle, thereby further improving the safety performance of the battery.
[0096] In one example, h2 ≥ h1.
[0097] In one example, h2>h1. Controlling the thickness of the second ceramic layer to be greater than the thickness of the first ceramic layer can effectively prevent the black spot lithium precipitation phenomenon in the middle of the pole piece, while maintaining the electrolyte retention in the middle area of the battery within a suitable range, thereby ensuring that the battery has a high mass energy density.
[0098] In one example, h2 = h1. The thickness of the second ceramic layer is controlled to be equal to the thickness of the first ceramic layer, which can effectively prevent the black spot lithium precipitation phenomenon in the middle of the pole piece while ensuring that the mass energy density meets the battery requirements.
[0099] In one example, 0.5 μm≤h1≤2 μm (eg, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, or 2 μm).
[0100] In one example, 1 μm≤h2≤10 μm (eg, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).
[0101] In one example, h2>h1, 0.5 μm≤h1≤2 μm, and 1 μm≤h2≤10 μm.
[0102] In one example, the thickness of the first ceramic layer is h1, in μm, 0.5 μm ≤ h1 ≤ 2 μm, the thickness of the second ceramic layer is h2, in μm, 1 μm ≤ h2 ≤ 10 μm, and h2>h1, then the diaphragm satisfies the following relationship: A = h1 × D1 × BET1, B = h2 × D2 × BET2, then 0.5 ≤ B / A ≤ 11, 0.1 μm ≤ D1 ≤ 0.5 μm, 8 μm 2 / g≤BET1≤20m 2 / g, 0.6μm≤D2≤1.4μm, 2m 2 / g≤BET2≤7m 2 / g.
[0103] In one example, the coverage of the adhesive layer in the vertical projection direction of the ceramic layer and / or the substrate is C%, the thickness of the adhesive layer is h4, and the unit is μm, then the diaphragm satisfies the following relationship: 0<{w2×(C×h4)} / (h1×w1)≤14 (for example, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14). Controlling the diaphragm to satisfy the above relationship can improve the liquid absorption capacity of the middle area of the diaphragm while ensuring good adhesion between the diaphragm and the electrode, and further effectively improve the problem of black spot lithium precipitation, improve the cycle performance and safety performance of the battery, and extend the service life of the battery.
[0104] In one example, C% is 20%-70% (e.g., 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, or 70%). Among them, the coverage rate of the adhesive layer on the vertical projection direction of the ceramic layer and / or the substrate is expressed as follows: when the adhesive layer is located on the surface of the ceramic layer, the adhesive layer is located on the surface of the second ceramic layer, so C% is the proportion of the coverage area of the adhesive layer in the vertical projection direction of the second ceramic layer based on the surface area of the second ceramic layer; when the adhesive layer is located on the surface of the substrate, C% is the proportion of the coverage area of the adhesive layer in the vertical projection direction of the substrate based on the surface area of the substrate; when the adhesive layer is located on the surfaces of the ceramic layer and the substrate, that is, the surface of the second ceramic layer and the surface of the substrate are both coated with the adhesive layer, then C1% is the proportion of the coverage area of the adhesive layer in the vertical projection direction of the second ceramic layer based on the surface area of the second ceramic layer, C2% is the proportion of the coverage area of the adhesive layer in the vertical projection direction of the substrate based on the surface area of the substrate, and C1%=C2%, then C%=C1%=C2%.
[0105] In one example, 0<h4≤5 μm (eg, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, or 5 μm).
[0106] In one example, the diaphragm satisfies the following relationship: 0<{w2×(C×h4)} / (h1×w1)≤14, and C% is 20%-70%, and 0<h4≤5μm.
[0107] In one example, the substrate includes one or more polymer materials such as polypropylene (PP), polyethylene (PE), polypropylene (PP), polyethylene (PE), PET, PI, PMIA, PVDF and PBO.
[0108] In one example, the thickness h3 of the substrate is 4 μm-16 μm (e.g., 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or 16 μm). Controlling the thickness of the substrate within the above range can ensure that the battery has a more stable cycle performance, higher safety performance and higher energy density.
[0109] In one example, the thickness h3 of the substrate is 5 μm-7 μm.
[0110] In one example, the first ceramic layer further includes a first binder.
[0111] In one example, the first binder includes one or more of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA).
[0112] In one example, based on the total weight of the first ceramic layer, the weight content of the first ceramic particles is 90%-99% (for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%), and the weight content of the first binder is 1%-10% (for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%).
[0113] In one example, based on the total weight of the first ceramic layer, the weight content of the first ceramic particles is 96%-98%, and the weight content of the first binder is 2%-4%.
[0114] In one example, the second ceramic layer further includes a second binder.
[0115] In one example, the second binder includes one or more of polyvinylidene fluoride (PVDF) and polymethyl methacrylate (PMMA).
[0116] In one example, based on the total weight of the second ceramic layer, the weight content of the second ceramic particles is 90%-99% (for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%), and the weight content of the second binder is 1%-10% (for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%).
[0117] In one example, based on the total weight of the second ceramic layer, the weight content of the second ceramic particles is 96%-98%, and the weight content of the second binder is 2%-4%.
[0118] In one example, the coating layer includes one or more of polyvinylidene fluoride, polyvinylidene fluoride-polyhexafluoropropylene copolymer, polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyimide, polyvinyl pyridine, polyvinyl pyrrolidone, styrene-butadiene rubber, polyvinylidene fluoride, acrylonitrile-butadiene rubber, ethylene-propylene-diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butene rubber, fluorine-containing rubber, styrene-butadiene rubber, carboxymethyl cellulose (CMC), starch, aramid resin, polyacrylic acid and hydroxypropyl cellulose.
[0119] A second aspect of the present invention provides a lithium ion battery, which includes the separator described in the first aspect of the present invention.
[0120] The materials of the lithium-ion battery except the separator can be prepared according to the methods in the art, and can achieve the effect of improving the cycle performance and safety performance.
[0121] In one example, the lithium-ion battery includes an electrolyte, the electrolyte includes ethyl difluoroacetate, and the weight content of the ethyl difluoroacetate is Ewt% based on the total weight of the electrolyte. Then, the lithium-ion battery satisfies the following relationship: 0.001≤K1×E / K2≤0.9.
[0122] Since the porosity of the second ceramic layer is relatively small, it is not easy for the electrolyte to penetrate into the first ceramic layer located underneath. Using ethyl difluoroacetate as an electrolyte additive helps to reduce the viscosity and surface tension of the electrolyte. When the above relationship is satisfied, the permeability and wettability of the electrolyte in the second ceramic can be improved. At the same time, the additive ethyl difluoroacetate can also make the interface between the diaphragm and the electrolyte have the same properties, thereby reducing the impedance and polarization of the interface, thereby improving the cycle stability of the battery.
[0123] In one example, Ewt% is 0.1wt%-10wt% (e.g., 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%).
[0124] In one example, Ewt% is 3wt%-6wt%.
[0125] In one example, the electrolyte further includes a lithium salt and an organic solvent.
[0126] In one example, the lithium salt includes one of lithium hexafluorophosphate (LiPF6), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB) and lithium tetrafluoroborate (LiBF4).
[0127] In one example, the organic solvent includes a mixture of one or more of diethyl carbonate (DEC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and propylene carbonate (PC).
[0128] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 10wt%-20wt%, and the weight content of the organic solvent is 70wt%-85wt%.
[0129] In one example, the lithium-ion battery further includes a positive electrode sheet and a negative electrode sheet. For example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductor and a negative electrode binder.
[0130] In one example, the negative electrode active material includes a graphite mixed material and / or graphite doped with at least one of hard carbon, soft carbon, silicon oxide and silicon carbon.
[0131] In one example, the negative electrode active material is a graphite mixed material doped with hard carbon, wherein the weight content of the hard carbon is 2wt%-10wt% (for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%) based on the total weight of the graphite mixed material.
[0132] In one example, based on the total weight of the graphite mixed material, the weight content of the hard carbon is 3wt%-5wt%.
[0133] In one example, the negative electrode conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber and carbon nanotube.
[0134] In one example, the negative electrode binder includes one or more of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, polyethylene oxide, and polyvinylidene fluoride.
[0135] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 80wt%-99.5wt% (for example, 80wt%, 85wt%, 90wt%, 95wt%, 99wt%, 99.5wt%), the weight content of the negative electrode conductor is 0.25wt%-10wt% (for example, 0.25wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%), and the weight content of the negative electrode binder is 0.25wt%-10wt% (for example, 0.25wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt%, 10wt%).
[0136] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 90wt%-99wt%, the weight content of the negative electrode conductor is 0.5wt%-5wt%, and the weight content of the negative electrode binder is 0.5wt%-5wt%.
[0137] In one example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, a positive electrode conductor and a positive electrode binder.
[0138] In one example, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate and lithium manganese iron phosphate.
[0139] In one example, the positive electrode conductive agent includes one or more of carbon nanotubes and carbon black.
[0140] In one example, the positive electrode binder includes one or more of polyvinylidene fluoride, acrylic acid-modified polyvinylidene fluoride, carboxylic acid-modified polyvinylidene fluoride, polyacrylic acid, polyacrylic acid copolymer, polymethyl methacrylate, and polyimide.
[0141] In one example, in one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 88wt%-98wt% (for example, 88wt%, 90wt%, 92wt%, 95wt% or 98wt%), the weight content of the positive electrode conductor is 1wt%-6wt% (for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or 6wt%), and the weight content of the positive electrode binder is 1wt%-6wt% (for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or 6wt%).
[0142] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 94.5wt%-97.5wt%, the weight content of the positive electrode conductor is 2wt%-5wt%, and the weight content of the positive electrode binder is 1.5wt%-4wt%.
[0143] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0144] The following examples are used to illustrate the separators of the present invention.
[0145] Example 1
[0146] (1) Preparation of ingredients
[0147] Substrate: Polyethylene porous base film, thickness 7μm;
[0148] First ceramic layer: first ceramic particles (alumina), 96 parts by weight, first binder (polyvinylidene fluoride), 4 parts by weight;
[0149] Second ceramic layer: second ceramic particles (alumina), 96 parts by weight, second binder (polyvinylidene fluoride), 4 parts by weight;
[0150] Adhesive layer: polyvinylidene fluoride (PVDF).
[0151] (2) Preparation of diaphragm
[0152] First ceramic slurry: first ceramic particles and a first binder are mixed, N-methylpyrrolidone is added, and the mixture is stirred evenly to obtain a first ceramic slurry, wherein the solid content of the first ceramic slurry is 40%-50%.
[0153] Second ceramic slurry: After mixing the second ceramic particles and the second binder, N-methylpyrrolidone is added, and the mixture is stirred evenly to obtain the second ceramic slurry. In order to ensure that the second ceramic slurry has high fluidity, the solid content of the second ceramic slurry is 30%-40%.
[0154] First, the first ceramic slurry is coated on one side of the substrate, the coating thickness is 1 μm, the coating width is half the width of the substrate, the coating temperature is controlled at 60°C, and after drying, the first ceramic layer is formed, and then the second ceramic slurry is coated on the surface of the coated first ceramic layer and the uncoated position on the substrate, the coating thickness is 2 μm, because the second ceramic slurry has high fluidity and large particles, even if the middle position has been coated with the first ceramic layer, the surface of the entire ceramic layer can still remain relatively flat after coating, and the coating temperature is also maintained at 60°C to obtain the second ceramic layer. Finally, the coating layer is coated on the surface of the second ceramic layer and the surface of the substrate. The coating layer is gravure coated with water-based PVDF, the coating thickness is 1 μm, and the diaphragm is obtained after drying. See Table 1-1, Table 1-2 and Table 1-3 for details. The calculation formula is as follows: A=h1×D1×BET1=1.5×0.4×15=9, B=h2×D2×BET2=2×1×5=10, B / A=10 / 9=1.11; {w2×(C×h4)} / (h1×w1)={90×(56%×2)} / (1.5×45)=1.5; K1×E / K2=55×4% / 27=0.0815.
[0155] Example 2 Group
[0156] This group of embodiments is used to illustrate the impact produced when the liquid absorption rate of the first ceramic layer changes.
[0157] This embodiment group is carried out with reference to the embodiment 1, except that the liquid absorption rate of the first ceramic layer is changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.
[0158] Example 3 Group
[0159] This group of embodiments is used to illustrate the influence produced when the liquid absorption rate of the second ceramic layer changes.
[0160] This embodiment group is carried out with reference to the embodiment 1, except that the liquid absorption rate of the second ceramic layer is changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.
[0161] Example 4 Group
[0162] This group of embodiments is used to illustrate the impact produced when the projection pattern of the first ceramic layer changes.
[0163] This embodiment group is carried out with reference to the embodiment 1, except that the projection pattern of the first ceramic layer is changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.
[0164] Example 5 Group
[0165] This group of embodiments is used to illustrate the impact when the ratio of the area of the coated area to the blank area is changed.
[0166] This embodiment group is carried out with reference to the embodiment 1, except that the area ratio of the coating area to the blank area is changed, see Table 1-1, Table 1-2 and Table 1-3 for details.
[0167] Example 6
[0168] Refer to Example 1, except that h1=h2, see Table 1-1, Table 1-2 and Table 1-3 for details.
[0169] Example 7 Group
[0170] This group of examples is used to illustrate the effects produced when the weight content of ethyl difluoroacetate in the electrolyte changes.
[0171] This example group was carried out with reference to Example 1, except that the weight content of ethyl difluoroacetate in the electrolyte was changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.
[0172] Example 8 Group
[0173] This group of embodiments is used to illustrate the impact when the coverage of the adhesive layer in the vertical projection direction of the ceramic layer or the substrate changes.
[0174] This embodiment group is carried out with reference to embodiment 1, except that the coverage of the coating layer in the vertical projection direction of the ceramic layer or the substrate is changed, see Table 1-1, Table 1-2 and Table 1-3 for details.
[0175] Example 9
[0176] Refer to Example 1, except that w2 / w1 is changed, see Table 1-1, Table 1-2 and Table 1-3 for details.
[0177] Example 10 Group
[0178] This group of embodiments is used to illustrate the impact produced when the materials of the first ceramic particles and the second ceramic particles are changed.
[0179] This embodiment group is carried out with reference to the embodiment 1, except that the materials of the first ceramic particles and the second ceramic particles are changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.
[0180] Embodiment 11
[0181] The method is carried out in accordance with Example 1, except that some parameters of the first ceramic layer and the second ceramic layer are changed, as shown in Table 1-1, Table 1-2 and Table 1-3 for details.
[0182] Example 12
[0183] The method is carried out in accordance with Example 1, except that the thickness of the first ceramic layer, the thickness of the adhesive layer and the coverage of the adhesive layer in the vertical projection direction of the ceramic layer or the substrate are changed. For details, see Table 1-1, Table 1-2 and Table 1-3.
[0184] Example 13
[0185] Refer to Example 1, except that the weight proportion of the first binder in the first ceramic layer and the weight proportion of the second binder in the second ceramic layer are adjusted, and the liquid absorption rate, porosity and air permeability of the first ceramic layer and the second ceramic layer are changed. For details, see Table 1-1, Table 1-2 and Table 1-3.
[0186] Comparative Example 1
[0187] The same process is carried out as in Example 1, except that the second ceramic layer is replaced by the first ceramic layer.
[0188] Comparative Example 2
[0189] The same process is carried out as in Example 1, except that the first ceramic layer is replaced by the second ceramic layer.
[0190] Comparative Example 3
[0191] The same procedure is carried out as in Example 1, except that the first ceramic layer and the second ceramic layer are interchanged.
[0192] Table 1-1
[0193]
[0194]
[0195]
[0196] *Same as Example 1.
[0197] Table 1-2
[0198]
[0199]
[0200] *Same as Example 1.
[0201] Table 1-3
[0202]
[0203]
[0204]
[0205] Preparation Example
[0206] The separators obtained in the examples and comparative examples were distributed to prepare batteries according to the following method.
[0207] (1) Positive electrode
[0208] Positive electrode active material: lithium nickel cobalt manganese oxide, 96 parts by weight;
[0209] Positive electrode conductive agent: carbon black, 2.5 parts by weight;
[0210] Positive electrode binder: polyvinylidene fluoride, 1.5 parts by weight.
[0211] The positive electrode active material, positive electrode conductive agent, positive electrode binder and solvent N-methylpyrrolidone (NMP) are uniformly mixed to obtain positive electrode slurry, and the positive electrode slurry is uniformly coated on both sides of the positive electrode current collector to form a positive electrode active material layer, and the coated positive electrode sheet is baked to obtain a positive electrode sheet.
[0212] (2) Negative electrode
[0213] Negative electrode active material: 96 parts by weight of a graphite mixed material with hard carbon (wherein the weight ratio of graphite to hard carbon is 97:3);
[0214] Negative electrode conductive agent: conductive carbon black, 1.5 parts by weight;
[0215] Negative electrode binder: sodium carboxymethyl cellulose (CMC-Na), 1 part by weight, 1.5 parts by weight of styrene-butadiene latex.
[0216] The negative electrode active material, negative electrode binder, negative electrode binder and negative electrode conductive agent are mixed, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is evenly coated on both sides of the high-strength carbon-coated copper foil, and after drying at room temperature, it is transferred to an oven at 80°C for drying for 10 hours, and then rolled and cut to obtain a negative electrode sheet.
[0217] (3) Electrolyte
[0218] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), mix the organic solvent evenly, add ethyl difluoroacetate, and then quickly add fully dried lithium salt, stir for 10 hours to fully dissolve it, and the desired electrolyte can be obtained. Among them, lithium salt: lithium hexafluorophosphate, 16 parts by weight; organic solvent: (weight ratio of ethylene carbonate to dimethyl carbonate = 5:5) 80 parts by weight; ethyl difluoroacetate 4 parts by weight.
[0219] (4) Diaphragm
[0220] The separators obtained in the above-mentioned embodiments and comparative examples were used respectively.
[0221] (5) Preparation of lithium-ion batteries
[0222] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, the electrolyte of step (3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes.
[0223] Test Case
[0224] The batteries obtained from the embodiments and comparative examples were tested as follows:
[0225] 1. Test of battery cell capacity, thickness, volume energy density and weight energy density
[0226] Weigh the prepared finished battery at 25°C to obtain the battery weight;
[0227] The prepared finished battery was charged to full charge (100% SOC) at constant current and constant voltage at 25°C, with a charging current of 0.5C, charged to 4.2V, a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C, and the discharged capacity was recorded as the battery capacity;
[0228] The finished battery was charged to 30% SOC at 25°C, and the battery thickness was tested using 600g PPG.
[0229] Calculate volume energy density (Wh / L) = (battery capacity * platform voltage) / (battery length / width / thickness);
[0230] Calculate the weight energy density (Wh / Kg) = (battery capacity * platform voltage) / battery weight.
[0231] 2. Residual liquid volume
[0232] First, weigh the weight of the unfilled battery as M1, and then weigh the weight of the finished battery after formation, sorting and packaging as M2. The residual liquid amount M = M2-M1.
[0233] 3. Cycle capacity retention rate, expansion rate and lithium precipitation test
[0234] Cycle capacity retention rate: The prepared finished battery is charged to 4.2V at 3C at 25°C, the cut-off current is 0.05C, and the 10C discharge is discharged to 2.5V. The discharge capacity at this time is recorded as the initial capacity as the first charge and discharge cycle. After 500 cycles, the discharge capacity at this time is recorded as the final capacity. The battery capacity retention rate (%) = [final capacity / initial capacity] × 100%;
[0235] Expansion rate: The initial thickness is the thickness of the incoming battery. According to the above cycle, the cycle is repeated for 500 cycles. The thickness at the 500th cycle is tested, that is, the thickness at 3C charging to 4.2V and the cut-off current of 0.05C is the final thickness. The expansion rate (%) = [final thickness / initial thickness] × 100%;
[0236] Lithium precipitation: According to the above cycle, after 500 cycles, dissect the battery to confirm whether there are local black spots and lithium precipitation. If so, Fig.10 If black spots appear, the result is expressed as "lithium precipitation". If no black spots appear, such as Fig. 9 If the result is shown in the table, the result is expressed as "no lithium precipitation".
[0237] 4. Discharge temperature rise test
[0238] The prepared finished battery was charged to 4.2V at 0.5C current, with a cutoff current of 0.05C, and then discharged to 3V at 5C current, then charged to 4.2V at 0.5C current, with a cutoff current of 0.05C, and then discharged to 3V at 6C current, then charged to 4.2V at 0.5C current, with a cutoff current of 0.05C, and then discharged to 3V at 7C current. The maximum surface temperature of the battery during discharge was monitored and recorded throughout the process.
[0239] The obtained results are recorded in Table 2.
[0240] Table 2
[0241]
[0242]
[0243] It can be seen from Table 2 that the comparative examples and embodiments show that the residual liquid amount of the diaphragm of the embodiment is higher, the capacity retention rate of the battery is higher, and the lithium precipitation situation is significantly improved, which means that by controlling the liquid absorption rate of the first ceramic layer> the liquid absorption rate of the second ceramic layer, the separation of the electrolyte in the diaphragm is optimized, and the cycle stability and safety performance of the battery are improved.
[0244] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A diaphragm, characterized in that: The diaphragm includes a substrate, a ceramic layer located on one side or both sides of the substrate, and a rubber coating layer located on the surface of the substrate and / or on the surface of the ceramic layer. The ceramic layer includes a first ceramic layer and a second ceramic layer. The first ceramic layer is located in the middle area of the substrate surface, and the second ceramic layer is located in the edge area of the substrate surface or on the surface of the first ceramic layer and the edge area of the surface of the substrate. The liquid absorption rate of the first ceramic layer is greater than the liquid absorption rate of the second ceramic layer.
2. The diaphragm according to claim 1, wherein The width of the first ceramic layer is w1, in μm, and the width of the substrate is w2, in μm, then the diaphragm satisfies the following relationship: w1≥w2 / 2; and / or, the liquid absorption rate of the first ceramic layer is 100%-200%; And / or, the liquid absorption rate of the second ceramic layer is 40%-110%.
3. The diaphragm according to claim 1, wherein The projection formed by the first ceramic layer on the surface of the substrate is a regular pattern or an irregular pattern; preferably, the projection formed by the first ceramic layer on the surface of the substrate is a square, stripe, circle, ellipse, polygon or irregular shape; and / or, the projection formed by the first ceramic layer on the surface of the substrate is a continuous pattern or a discontinuous pattern along the length direction of the diaphragm; And / or, the first ceramic layer includes a plurality of periodically arranged coating areas and blank areas, wherein the coating area is the first ceramic layer, the coating area corresponds to the plane area of the wound battery cell, and the blank area corresponds to the bending area of the wound battery cell; Preferably, the ratio of the area of the coated area to the area of the blank area is (50%-100%):(50%-0), more preferably (70%-100%):(30%-0).
4. The diaphragm according to claim 1, wherein The first ceramic layer includes first ceramic particles, the second ceramic layer includes second ceramic particles, and the liquid absorption rate of the first ceramic particles is greater than the liquid absorption rate of the second ceramic particles; and / or, the liquid absorption rate of the first ceramic particles is 100%-200%; and / or, the liquid absorption rate of the second ceramic particles is 40%-100%; and / or, the first ceramic particles include one or more of aluminum oxide, magnesium oxide, silicon oxide, titanium dioxide, zirconium dioxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, magnesium nitride, tin dioxide, magnesium hydroxide, boehmite and calcium carbonate; and / or, the second ceramic particles include one or more of aluminum oxide, magnesium oxide, silicon oxide, titanium dioxide, zirconium dioxide, zinc oxide, barium sulfate, boron nitride, aluminum nitride, magnesium nitride, tin dioxide, magnesium hydroxide, boehmite and calcium carbonate; And / or, the first ceramic particles include particles having a spherical honeycomb through-hole structure; and / or, the average particle size D1 of the first ceramic particles is less than the average particle size D2 of the second ceramic particles; And / or, the specific surface area BET1 of the first ceramic particles is greater than the specific surface area BET2 of the second ceramic particles.
5. The diaphragm according to any one of claims 1 to 4, wherein The porosity of the first ceramic layer is greater than the porosity of the second ceramic layer; And / or, the porosity K1 of the first ceramic layer is 40%-90%; and / or, the porosity K2 of the second ceramic layer is 10%-40%; And / or, the air permeability of the first ceramic layer is 20s / 100ml-100s / 100ml; And / or, the air permeability of the second ceramic layer is 170s / 100ml-370s / 100ml.
6. The diaphragm according to claim 4, wherein The thickness of the first ceramic layer is h1, in μm, and the thickness of the second ceramic layer is h2, in μm, and the diaphragm satisfies the following relationship: A=h1×D1×BET1, B=h2×D2×BET2, then 0.5≤B / A≤11; and / or, 0.1 μm ≤ D1 ≤ 0.5 μm; and / or, 8m 2 / g≤BET1≤20m 2 / g; and / or, 0.6 μm ≤ D2 ≤ 1.4 μm; and / or, 2m 2 / g≤BET2≤7m 2 / g.
7. The diaphragm according to claim 6, wherein: h2 ≥ h1; and / or, 0.5 μm ≤ h1 ≤ 2 μm; And / or, 1μm≤h2≤10μm.
8. The diaphragm according to claim 6 or 7, wherein: The coverage of the coating layer in the vertical projection direction of the ceramic layer or the substrate is C%, the thickness of the coating layer is h4, in μm, and the diaphragm satisfies the following relationship: 0<{w2×(C×h4)} / (h1×w1)≤14; Preferably, C% is 20%-70%; Preferably, 0<h4≤5μm.
9. A lithium ion battery, characterized in that: The lithium ion battery comprises the separator according to any one of claims 1 to 8.
10. The lithium ion battery according to claim 9, wherein: The lithium ion battery includes an electrolyte, and the electrolyte includes ethyl difluoroacetate. Based on the total weight of the electrolyte, the weight content of the ethyl difluoroacetate is Ewt%, and the lithium ion battery satisfies the following relationship: 0.001≤K1×E / K2≤0.
9.
11. The lithium ion battery according to claim 10, wherein: Ewt% is 0.1wt%-10wt%, preferably 3%wt%-6%wt%.
Citation Information
Patent Citations
Lithium ion battery diaphragm, preparation method thereof and lithium ion battery
CN113394516A
Composite diaphragm and battery
CN114221093A
Separator, battery cell, battery and electrical device
WO2024159529A1
Cited By
Secondary battery, preparation method thereof, energy storage system and electric equipment
CN120221930A
Composite ceramic coated diaphragm and method for manufacturing the same
CN122782112A
Separator and battery
WO2026179775A1
